Clinical outcomes following esophagectomy for benign esophageal diseases: a single center experience - Jesudason, Jeya Sudhahar; Chandrabose, Karpagavel (International Surgery Journal, 2019)
Background: Surgery is the treatment option for wide range of benign esophageal diseases. But there are very few studies on Indian population, documenting the profile and clinical outcome of esophageal disease treated by surgical intervention. Hence author undertook a study to determine the clinical outcomes following esophagectomy for benign esophageal diseases. Methods: The current study was a prospective observational study, conducted in Velammal Medical College, Madurai. Data collection was done for 6 years from January 2012 to December 2017. Patients diagnosed with benign esophageal diseases were enrolled. The surgical procedures performed and outcomes were documented. Mean and standard deviation were used to summarize numeric variables, number and percentage were used to summarize categorical variables. Results: A total of 20 cases were included, with 11 men and 9 women. The mean age was 42.6±8.3 years. Dysphagia (90%) was the most common presentation, followed by heart burn (58%), regurgitation (40%) and chest pain (25%). Boerhaave syndrome (25%) was the most common diagnosis followed by foreign body perforation in 2(10%) patients. Corrosive stricture, peptic stricture, perforation following pneumatic dilatation and end stage achalasia were present in 2(10%) patients each. Jejunostomy and pyloroplasty were the procedure done in all cases. Stomach was the conduit used in 90% of patients. The conduit placement was done in the posterior mediastinum. The duration of the hospital stay ranged from 10 to 35 days. Mortality rate was 10%. Pulmonary morbidity (40%) was the most common post-operative complication, followed by wound infection (20%). Anastomotic stricture occurred among 30% of subjects. Conclusions: There is a high probability of occurrence complications following esophagectomy for benign disease. Clinicians must be aware of incidence of various complications, to be able to minimize and manage them effectively.